The coexistence of acorns with different maturation patterns explains acorn production variability in cork oak. - Pons, Josep; Pausas, Juli G. (Oecologia, 2012)
In dry areas such as Mediterranean ecosystems, fluctuations in seed production are typically explained by resource (water) availability. However, acorn production in cork oak (Quercus suber) populations shows a very low relationship to weather. Because cork oak trees produce acorns with different maturation patterns (annual and biennial), we hypothesized that acorn production in coexisting individuals with a different dominant acorn maturation type should respond differently to climatic factors and that disaggregating the trees according to their acorn-maturation pattern should provide a more proximal relation to weather factors. We assessed acorn production variability in fragmented cork oak populations of the eastern Iberian Peninsula by counting the total number of acorns in 155 trees during an 8-year period. An initial assessment of acorn production variability in relation to weather parameters yielded very low explained variance (7%). However, after the trees were grouped according to their dominant acorn maturation pattern, weather parameters were found to account for 44% of the variability in acorn crops, with trees with annual acorns exhibiting mast fruiting in years with reduced spring frost and shorter summer droughts and trees with biennial acorns showing the opposite pattern. Thus, conditions that negatively affect annual production could be beneficial for biennial production (and vice versa). The results highlight the importance of the resource-matching hypothesis for explaining acorn production in Quercus suber and suggest that different seed maturation types within a population may allow the species to deal with highly variable weather conditions. They also emphasize the importance of understanding acorn maturation patterns for interpreting masting cycles.
The following values have no corresponding Zotero field: accession-num: 22246473
Keywords: biomass; Evergreen oaks; Fruit; Fruit: growth & development; Hypothesis; Masting; Mediterranean Region; Mediterranean woodlands; Quercus; Quercus suber; Quercus: growth & development; Weather

Not only size matters: Acorn selection by the European jay (Garrulus glandarius) - Pons, Josep; Pausas, Juli G. (Acta Oecologica, 2007)
A strong selection for acorn characteristics is expected to have evolved in the mutualistic relationship between the European jay (Garrulus glandarius) and the oak (Quercus spp.). Bossema’s pioneer work suggested that jays do not select acorns randomly, but rather they preferentially select some size and species. Preference for some seeds over others may have implications on plant community dynamics by conferring advantages (or disadvantages) on the selected (avoided) seed characteristics. In this paper we test to what extent jays select acorns by species and/or by size and the relation between these two traits in Mediterranean oak species. The experiments consist of a set of ﬁeld tests in which acorns from four different coexisting Mediterranean oak species (Quercus ilex, Quercus faginea, Quercus suber, and Quercus coccifera) were placed in artiﬁcial feeders accessible to wild jays. The acorns were previously measured to control individual acorn characteristics. Using video-recording techniques, we followed jay activity and the fate of each acorn (sequence of acorn selection and method of transport). Q. ilex acorns were preferred over other acorns, and Q. coccifera acorns were avoided when other acorns were available. Preference for Q. faginea and Q. suber acorns was intermediate, that is, they were preferred over Q. coccifera acorns but not over Q. ilex acorns. Large acorns were also preferred although acorn species selection was stronger than size selection. Jays selected species and size both by visual means and by using acorn area as an indicator of size. Acorns wider than 17–19 mm were carried in the bill because of throat limitation. Our results conﬁrm Bossema’s study on temperate oaks and extend it to Mediterranean oak species, revealing implications on mixed oak forest dynamics.
Keywords: Acorn selection; Garrulus glandarius; Mediterranean oak forests; Mutualism; Quercus coccifera; Quercus faginea; Quercus ilex; Quercus suber; Regeneration

Not only size matters: Acorn selection by the European jay (Garrulus glandarius) - Pons, Josep; Pausas, Juli G (Acta Oecologica, 2007)
A strong selection for acorn characteristics is expected to have evolved in the mutualistic relationship between the European jay (Garrulus glandarius) and the oak (Quercus spp.). Bossema’s pioneer work suggested that jays do not select acorns randomly, but rather they preferentially select some size and species. Preference for some seeds over others may have implications on plant community dynamics by conferring advantages (or disadvantages) on the selected (avoided) seed characteristics. In this paper we test to what extent jays select acorns by species and/or by size and the relation between these two traits in Mediterranean oak species. The experiments consist of a set of ﬁeld tests in which acorns from four different coexisting Mediterranean oak species (Quercus ilex, Quercus faginea, Quercus suber, and Quercus coccifera) were placed in artiﬁcial feeders accessible to wild jays. The acorns were previously measured to control individual acorn characteristics. Using video-recording techniques, we followed jay activity and the fate of each acorn (sequence of acorn selection and method of transport). Q. ilex acorns were preferred over other acorns, and Q. coccifera acorns were avoided when other acorns were available. Preference for Q. faginea and Q. suber acorns was intermediate, that is, they were preferred over Q. coccifera acorns but not over Q. ilex acorns. Large acorns were also preferred although acorn species selection was stronger than size selection. Jays selected species and size both by visual means and by using acorn area as an indicator of size. Acorns wider than 17–19 mm were carried in the bill because of throat limitation. Our results conﬁrm Bossema’s study on temperate oaks and extend it to Mediterranean oak species, revealing implications on mixed oak forest dynamics.
Keywords: Acorn selection; Garrulus glandarius; Mediterranean oak forests; Mutualism; Quercus coccifera; Quercus faginea; Quercus ilex; Quercus suber; Regeneration

Rodent acorn selection in a Mediterranean oak landscape - Pons, Josep; Pausas, Juli G (Ecological Research, 2006)
Quercus suber, Quercus ilex and Quercus coccifera (Cork, Holm and Kermes oaks, respectively) are common evergreen oak species that coexist in the landscapes of the western part of the Mediterranean basin. Rodents are the main acorn predators and thus one of the main factors for understanding recruitment patterns in oaks. In this paper we analyse to what extent mice prefer acorns from one oak species over another in three oak species studied using acorn removal experiments and video tape recordings. Twenty labelled acorns from each of the three Quercus species (60 acorns) were placed in 40 cm·40 cm quadrats on each plot. Because selection might vary as a result of the vegetation context, we performed the trials in the ﬁve main vegetation types within the study area (four replicates in each vegetation type) in order to control for habitat inﬂuences on rodent acorn preferences (a total of 20 plots). The removal of 1,200 acorns occurred within 68 days. Mice removed 98.7% of the acorns. Q. ilex acorns were preferred over Q. suber and Q. coccifera in all vegetation types except in pine forest, where no acorn preferences were detected. Acorn removal rates diﬀered with vegetation type, correlating positively with shrub cover. The distance at which acorns were displaced by rodents (mean =4.6 m±5.1 SD) did not diﬀer between acorn species, but varied among vegetation types. Bigger acorns of Q. coccifera were selected only after Q. ilex and Q. suber acorns were depleted, while no size selection was detected for the latter two species. Thus, we conclude that rodents show preference for some oak acorns and that landscape context contributes signiﬁcantly to rodent activities and decisions.
Keywords: Apodemus sylvaticus; Quercus coccifera; Quercus ilex; Quercus suber; Removal rates; Retrieval distances; Size selection

Rodent acorn selection in a Mediterranean oak landscape - Pons, Josep; Pausas, Juli G. (Ecological Research, 2006)
Quercus suber, Quercus ilex and Quercus coccifera (Cork, Holm and Kermes oaks, respectively) are common evergreen oak species that coexist in the landscapes of the western part of the Mediterranean basin. Rodents are the main acorn predators and thus one of the main factors for understanding recruitment patterns in oaks. In this paper we analyse to what extent mice prefer acorns from one oak species over another in three oak species studied using acorn removal experiments and video tape recordings. Twenty labelled acorns from each of the three Quercus species (60 acorns) were placed in 40 cm·40 cm quadrats on each plot. Because selection might vary as a result of the vegetation context, we performed the trials in the ﬁve main vegetation types within the study area (four replicates in each vegetation type) in order to control for habitat inﬂuences on rodent acorn preferences (a total of 20 plots). The removal of 1,200 acorns occurred within 68 days. Mice removed 98.7% of the acorns. Q. ilex acorns were preferred over Q. suber and Q. coccifera in all vegetation types except in pine forest, where no acorn preferences were detected. Acorn removal rates diﬀered with vegetation type, correlating positively with shrub cover. The distance at which acorns were displaced by rodents (mean =4.6 m±5.1 SD) did not diﬀer between acorn species, but varied among vegetation types. Bigger acorns of Q. coccifera were selected only after Q. ilex and Q. suber acorns were depleted, while no size selection was detected for the latter two species. Thus, we conclude that rodents show preference for some oak acorns and that landscape context contributes signiﬁcantly to rodent activities and decisions.
Keywords: Apodemus sylvaticus; Quercus coccifera; Quercus ilex; Quercus suber; Removal rates; Retrieval distances; Size selection